The Contribution of Waqf on Poverty Alleviation through Digital Platforms: A Case of Indonesia - Ardhika Wahyu Kuncoro; Ahmad bin Muhammad Husni; Elina Adi Wijayanti; Ahmad Fanani (Shirkah: Journal of Economics and Business, 2021)
Today, poverty is a crucial issue and has a great impact in social and economic development. Waqf (charitable endowment) is one of the sources of Islamic economic system, which refers to the voluntary charity. Waqf has a unique presence in Islam and could potentially alleviate poverty. It was reflected in the historical lesson since prophet Muhammad (PBUH) and his companions developed a system where rich people could donate their wealth for the society development. This concept, nowadays, is adopted by developing a Waqf system that integrates digital technology. Concerning on this issue, the present study aims to snapshot a poverty situation and portray the grand design of digital Waqf system in alleviating the poverty in Indonesia. Under the procedure of qualitative approach, this study employs document analysis and observation of all instruments related to Waqf. The results show that Waqf plays an important role in decreasing poverty in Indonesia. By utilizing digital platforms, the collection of Waqf funds is effective and widely spread to the Muslim community within the country. The results suggest that digital Waqf system has a crucial role and potentially contributes to the sustainable economic development of a developing country, particularly Indonesia. This study can be used in financial inclusion through the application of digital Waqf to alleviate poverty.